The Effect of Intense Physical Exercise on Iron Deficiency - Lewalski, Tymon; Słuchocka, Joanna; Florczyk, Martyna; Lewalski, Oskar; Płuciennik, Lidia; Jeruć, Klaudia (Quality in Sport, 2026)
Intense physical exercise, especially when performed frequently or for prolonged durations, can disturb iron balance through a combination of increased demand, increased loss, and impaired absorption. The strongest evidence comes from endurance sport, military training, and periods of intensified loading, where iron deficiency without anemia and overt iron-deficiency anemia are both common clinical problems. Mechanisms include exercise-induced inflammation and hepcidin upregulation, intravascular hemolysis, gastrointestinal microischemia with occult blood loss, hematuria, sweat losses, menstrual blood loss, low energy availability, and the amplified iron demand of altitude-related erythropoiesis. Importantly, the hematologic response to training also includes plasma volume expansion, which can mimic anemia without true iron deficiency and complicate interpretation. In athletes, clinically meaningful iron deficiency may present before hemoglobin falls, with fatigue, impaired recovery, lower maximal oxygen uptake, diminished training quality, and reduced work efficiency. Diagnosis therefore requires more than hemoglobin alone and should integrate ferritin, transferrin saturation, inflammatory context, and where indicated soluble transferrin receptor or reticulocyte indices. Management begins with confirmation of true deficiency and identification of the mechanism, followed by dietary optimization, oral iron when indicated, and selective use of parenteral iron in carefully chosen cases. This review summarizes the physiology linking exercise to iron homeostasis, identifies athlete groups at highest risk, distinguishes pseudoanemia from true deficiency, and provides a practical framework for diagnosis, prevention, and treatment.